(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Respiratory and cardiac arrest are life-threatening emergencies that require rapid treatment. In the general public, including those in Lamalaka Village, the level of knowledge and first aid skills for these conditions needs to be improved to support an effective response before medical personnel arrive. Based on data from the Lasepang Community Health Center and the Public Safety Center (PSC) of the Lontara 119 Bantaeng UPT, cardiac and respiratory arrest cases are urgent in emergency management, but education regarding Basic Life Support (BLS) for the community is still limited. To address this problem, an education program and BLS practical training were conducted for residents of Lamalaka Village using a pre-test, material education, practical simulations, and a post-test as a learning evaluation. This program adopted the 2020 American Heart Association (AHA) standards, which are scientifically proven to improve BLS skills in the general public. The goal of this activity is to improve the community’s knowledge and skills in providing first aid for respiratory and cardiac arrest cases, thereby increasing the chances of survival for emergency victims. The evaluation showed an increase in the average knowledge score of participants from 71 to 96.2, with a significance value of p = 0.000 (p < 0.05). Participants also actively participated in the BHD simulation practice. Therefore, this BHD education and simulation program has proven effective in increasing community preparedness and rapid response to emergencies and has the potential to be replicated in other communities to expand the positive impact on health and safety. Keywords: Basic Life Support, First Aid, Cardiac Arrest, Respiratory Arrest Kondisi henti napas dan henti jantung merupakan keadaan gawat darurat yang mengancam nyawa dan memerlukan penanganan cepat. Di masyarakat umum, termasuk Kelurahan Lamalaka, tingkat pengetahuan dan keterampilan pertolongan pertama terhadap kondisi tersebut perlu ditingkatkan untuk mendukung respons efektif sebelum tenaga medis tiba. Berdasarkan data dari Puskesmas Lasepang dan Public Safety Center (PSC) UPT Lontara 119 Bantaeng, kasus henti jantung dan henti napas termasuk urgensi dalam penanganan kegawatdaruratan, namun edukasi mengenai Bantuan Hidup Dasar (BHD) bagi masyarakat masih terbatas. Untuk mengatasi persoalan tersebut, dilakukan program edukasi dan pelatihan praktik BHD kepada warga Kelurahan Lamalaka dengan metode pre-test, edukasi materi, simulasi praktik, dan post-test sebagai evaluasi pembelajaran. Program ini mengadopsi standar American Heart Association (AHA) 2020 yang terbukti secara ilmiah meningkatkan keterampilan BHD pada masyarakat umum. Tujuan kegiatan ini adalah meningkatkan pengetahuan dan keterampilan masyarakat dalam memberikan pertolongan pertama pada kasus henti napas dan henti jantung sehingga memperbesar peluang keselamatan korban kegawatdaruratan. Evaluasi menunjukkan peningkatan rata-rata skor pengetahuan peserta dari 71 menjadi 96,2 dengan nilai signifikansi p = 0,000 (p < 0,05). Peserta juga aktif mengikuti praktik simulasi BHD. Oleh karena itu, program edukasi dan simulasi BHD ini terbukti efektif meningkatkan kesiapsiagaan dan respons cepat masyarakat menghadapi kondisi darurat serta berpotensi direplikasi di komunitas lain untuk memperluas dampak positif kesehatan dan keselamatan. Kata Kunci: Bantuan Hidup Dasar (BHD), Pertolongan Pertama, Henti Napas dan Henti Jantung